Challenges of Activating Participatory Democracy in Algeria - Bakhti, Boubaker (Journal of Legal Studies and Researches, 2020)
Participatory democracy is a mechanism for achieving a good system of government, restoring confidence in government policies, and one of its outcomes is dialogue and finding solutions to differences that occur, bringing views peacefully, and achieving national integration. Although the legal foundations for participatory democracy exist, they will remain a set of obstacles and challenges that may prevent their implementation and give them the value that is expected of them.